Combining the microbial calcite precipitation process with biochar in order to improve nickel remediation. (April 2019) - Zhang, Jing; Kumari, Deepika; Fang, Chaolin; Achal, Varenyam
Abstract: Microbially induced calcite precipitation (MICP) is a promising technology in the remediation of heavy metals, while biochar is a valuable adsorbent for its removal. In the present study, biochar was added to the MICP process to investigate its effect on the remediation of nickel (Ni). The MICP process immobilized 89% and 66% of Ni 2+ at initial concentrations of 50 and 100 mg L −1, respectively. However, biochar had an inhibitory effect on the calcite produced by Bacillus cereus NS4 and suppressed the Ni remediation. The mechanism of suppression by biochar was elucidated by scanning electron microscopy-energy dispersion spectrophotometry, Fourier transform infrared spectroscopy, and X-ray diffraction techniques. Biochar caused weakening of the adsorption bonds responsible for carbonate formation led to dissociation of the carbonate structure. This is the first study to combine biochar with the MICP process and provides reference data for better understanding of the mechanism of suppression of carbonate precipitation by biochar. Highlights: Biochar was amended in the MICP process to investigate its effect on the remediation of nickel. Biochar showed inhibitory effect on biogenic calcite and suppressed nickel remediation. FTIR and XRD revealed dissociation of carbonate structure after biochar amendment in MICP.